2006
DOI: 10.1557/jmr.2006.0172
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3scale development on iron aluminides

Abstract: The structure and phase of the Al 2 O 3 scale that forms on an Fe 3 Al-based alloy found between the bands. Extended oxidation produced a double-layered scale structure, with a continuous layer at the scale/alloy interface, and a / layer at the gas surface. The mechanism for the formation of Al 2 O 3 scales on iron aluminide alloys is discussed and compared to that for nickel aluminide alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…interface, and the a-Al 2 O 3 /metastable interface moved toward to the scale/metal interface. As mentioned in the introduction, metastable to a-Al 2 O 3 transformation was reported to occur at the scale/alloy interface [2,3,10,12,13]. In the present study, it was also confirmed that transformed a-Al 2 O 3 with relatively large grains was formed at the scale/alloy interface as shown in Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…interface, and the a-Al 2 O 3 /metastable interface moved toward to the scale/metal interface. As mentioned in the introduction, metastable to a-Al 2 O 3 transformation was reported to occur at the scale/alloy interface [2,3,10,12,13]. In the present study, it was also confirmed that transformed a-Al 2 O 3 with relatively large grains was formed at the scale/alloy interface as shown in Fig.…”
Section: Resultssupporting
confidence: 87%
“…Not only Cr, but also Fe and Ti should have this same effect on the transformation to a-Al 2 O 3 , since those elements also form corundum structure oxides, Fe 2 O 3 and Ti 2 O 3 , respectively. In fact, Fe was also frequently recognized to accelerate this Al 2 O 3 scale transformation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable -Al 2 O 3 has a corundum crystal structure. Thus, other corundum-structured oxides, such as Cr 2 O 3 and Fe 2 O 3 , can serve to facilitate -Al 2 O 3 nucleation, as has been reported for Fe-and Cr-containing alloys [4,25,26]. In those studies, cross-sectional TEM analysis strongly indicated that the -Al 2 O 3 nucleated initially at the scale/alloy interface.…”
Section: Introductionmentioning
confidence: 67%
“…The phase transformation behavior of thermally grown Al 2 O 3 scale formed on Fe-and Ni-based alloys has been widely investigated [6][7][8][9][10][11][12][13]. In these studies, different factors, such as atmospheres and alloy compositions affecting the phase transformation, were reported that, for example, reactive elements, such as Y, Hf, and Zr, slow the transformation [12,13], and Fe and/or Cr accelerate the transformation [6,11].…”
Section: Introductionmentioning
confidence: 99%